Analisis Pengaruh Faktor Fundamental Makro Ekonomi terhadap Indeks Harga Saham Gabungan (IHSG) - Wenny Ana Adnanti (Jurnal Ilmiah Aset, 2017)
This study aimed to analyze the influence of exchange rate, interest rates, and inflation simoultaneously and partially affect on CSPI. The method of analysis used in this study is the method of multiple linear regression analyzes were used with SPSS 16. The research used data monthly of Januari 2010 to December 2015 with 72 sample of data time series for each independent and dependent variabel. Data obtained from the Monthly Statistic, Indonesia Stock Exchange and Indonesian Financial Statistics of Bank Indonesia. Simoultan analysis show variable exchange rate , interest rates and inflation significanthly negative affect on Composite Stock Price Index (CSPI). Partial analysis shows exchange rate affect positive on CSPI, interest rate affect negative on CSPI and inflation does not affect on CSPI.